Niger: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty: Updated 2022-07-22 - Diao, Xinshen; Dorosh, Paul; Ellis, Mia; Pauw, Karl; Thurlow, James (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Mia Ellis, Karl Pauw, and James Thurlow, all with the International Food Policy Research Institute, Washington, DC. This is part of the Global Crisis Country Series.